Improved phenological escape can help temperate tree seedlings maintain demographic performance under climate change conditions. (5th June 2021) - Lee, Benjamin R.; Ibáñez, Inés
Abstract: Phenological escape, a strategy that deciduous understory plants use to access direct light in spring by leafing out before the canopy closes, plays an important role in shaping the recruitment of temperate tree seedlings. Previous studies have investigated how climate change will alter these dynamics for herbaceous species, but there is a knowledge gap related to how woody species such as tree seedlings will be affected. Here, we modeled temperate tree seedling leaf‐out phenology and canopy close phenology in response to environmental drivers and used climate change projections to forecast changes to the duration of spring phenological escape. We then used these predictions to estimate changes in annual carbon assimilation while accounting for reduced carbon assimilation rates associated with hotter and drier summers. Lastly, we applied these estimates to previously published models of seedling growth and survival to investigate the net effect on seedling demographic performance. Our models predict that temperate tree seedlings will experience improved phenological escape and, therefore, increased spring carbon assimilation under climate change conditions. However, increased summer respiration costs will offset the gains in spring under extreme climate change leading to a net loss in annual carbon assimilation and demographic performance. Furthermore, we found that annual carbon assimilation predictions depend strongly on the species of nearby canopy tree that seedlings were planted near, with all seedlings projected to assimilate less carbon (and therefore experience worse demographic performance) when planted near Quercus rubra canopy trees as opposed to Acer saccharum canopy trees. We conclude that changes to spring phenological escape will have important effects on how tree seedling recruitment is affected by climate change, with the magnitude of these effects dependent upon climate change severity and biological interactions with neighboring adults. Thus, future studies of temperate forest recruitment should account for phenological escape dynamics in their models. Abstract : Deciduous tree seedlings in temperate forests rely on phenological escape in spring to access light and assimilate positive carbon balances that allow them to survive and grow throughout the rest of the growing season. However, climate change is shifting leaf‐out phenology for seedlings and canopy trees alike and it is yet unknown if this will result in differences in access to spring light for understory trees. Here, we found that climate change will increase seedling access to light in spring, but that reduced summer precipitation and hotter temperatures will lead to net negative changes in seedling performance.